The Impact of Transformational Leadership on Employee Performance: An Intermediary Function of Organizational Commitment and Job Satisfaction - Indriasari, Ratna; Permatasari, Marisa; Khair, Otti Ilham; Yusuf, Achmad; Susi, Susi; Luthfi, Ahmad (Kawanua International Journal of Multicultural Studies, 2023)
This study explores the impact of transformational leadership on employee performance. Qualitative descriptive analysis is used to identify problem patterns and relationships between concepts. Literature analysis supplements the research by examining relevant journals and articles. Findings demonstrate a significant positive influence of transformational leadership on employee performance, motivating employees to achieve organizational goals effectively and efficiently. Organizational commitment and job satisfaction serve as mediators between transformational leadership and performance. Transformational leadership enhances performance by fostering increased commitment and job satisfaction. Employees who exhibit attachment to the organization and job satisfaction tend to perform better. Overall, transformational leadership positively influences employee performance, with organizational commitment and job satisfaction acting as mediators in this relationship.